RESTORATION OF LAND RESOURCES: LEGAL ASPECT - Zhmur, Nataliia; Seredenko, Liubov (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2023)
Purpose: comprehensive research and analysis of current legislation on the restoration of land resources. Research methods: a combination of general (analysis, synthesis, comparison, induction, deduction) and special research methods (systemic-functional, formal-logical, formal-legal) are applied. Results: the current legislation on the restoration of land resources was analyzed and researched; it was established that the legal regulation of restoration of land resources, legal relations regarding the restoration of lands and preservation of their fertility is a separate element of the subject of land law. Discussion: on the basis of a comprehensive analysis and research of the legal regulation of the restoration of land resources, the problems of the imperfection of the legislation were identified and ways of improvement were proposed, namely the development and adoption of a separate specialized act. This can be the Law of Ukraine «On Land Restoration», «Concept of Restoration of Ruined Soils», «Basic Principles of Land Legislation in the Field of Restoration and Reclamation of Land Resources», etc. In addition, state bodies and local self-government bodies should work on the implementation of programs to increase the legal awareness of Ukrainians, inculcate in them respect and self-responsibility for the used land resources.